1996
DOI: 10.1111/j.1468-3148.1996.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to People with Intellectual Disabilities Moving into Ordinary Houses: What the Neighbours Say1

Abstract: A study was conducted to measure the attitudes of immediate neighbours to people with intellectual disabilities who move from hospitals into ordinary houses. Some neighbours in the area under study had demonstrated overt hostility towards the newcomers. 83 neighbours of 17 established homes were interviewed once, and 67 neighbours of 9 planned homes were interviewed three times: before the newcomers arrived, within a month of their arrival, and one year later. It was found that the majority of the neighbours' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…open days and asking for volunteers), and the relative invisibility of residents on occasion. This seems to correspond with previous research that has also revealed that people make a distinction between attitudes towards a home for people with ID and attitudes to individual residents (Hudson-Allez & Barrett, 1996;Schwartz & Rabinovitz, 2001). Moreover, the observation that changing the living arrangements of people with ID from institutional to community care does not necessarily mean that all the habits of the old institution are shed (Overkamp, 2002;van Alphen et al, 2009) may therefore also refer to the habits in interacting with neighbours.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…open days and asking for volunteers), and the relative invisibility of residents on occasion. This seems to correspond with previous research that has also revealed that people make a distinction between attitudes towards a home for people with ID and attitudes to individual residents (Hudson-Allez & Barrett, 1996;Schwartz & Rabinovitz, 2001). Moreover, the observation that changing the living arrangements of people with ID from institutional to community care does not necessarily mean that all the habits of the old institution are shed (Overkamp, 2002;van Alphen et al, 2009) may therefore also refer to the habits in interacting with neighbours.…”
Section: Discussionsupporting
confidence: 78%
“…Using Hamilton's micro-neighbourhood design (as cited in Hudson-Allez & Barrett, 1996), people from the two houses on either side of a care facility, as well as the five houses opposite, and the three houses bordering the back of the property were invited. Using this design, neighbours who were likely to see or hear their neighbours with ID were included.…”
Section: Recruitment Of Informantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers blame the competencies of people with disabilities (notably a lack of social skills) and/or those of neighbourhood residents (Alphen et al, 2010); they refer to feelings of insecurity in people with disabilities due to negative experiences in the past such as name-calling and abuse (Alphen et al, 2009;Robertson et al, 2005). Researchers point at prejudice and negative community attitudes (Dijker et al, 2011;Hudson-Allez and Barret, 1996;Pittock and Potts, 1988). Researchers blame the lack of professional support (Alphen et al, 2010) or seek explanations in the developed environment, such as the manner in which people with disabilities are housed (non-congregate settings versus congregate settings) (Bostock and Gleeson, 2004), housing in weaker neighbourhoods with small apartments where proximity is a problem (Trappenburg, 2015), lack of community spirit in urban areas (Nicholson and Cooper, 2013) or a lack of common space (such as bordering gardens or a shared driveway) (Alphen et al, 2009(Alphen et al, , 2010Pittock and Potts, 1988).…”
Section: Sociological Theory and Research On Neighbourhood Behaviourmentioning
confidence: 99%